Degeneration of the lumbar intervertebral discs as a cause of root discomfort in the lumbar spine - Aneta Karło; Beniamin Szmelcer; Marlena Kontowicz; Patrycja Wszelaki; Daria Zaborna; Michał Wilczyński; Natalia Krakowska; Aleksander Florczak; Aleksandra Modlińska; Adrian Zwolinski; Klaudia Kwiatkowska; Paula Piątkowska; et al. (Kazimierz Wielki University, 2019)
Background: The change in the lifestyle of modern man and the related lack of physical activity caused that pain in the spine has become a civilization problem, covering an increasing population regardless of latitude. Degenerative changes of the spine, also in the lumbar region, are the most frequently diagnosed cause of patients' dysfunction. Material and methods: Analysis of available literature, articles in the Google Scholar and PubMed database using keywords: lumbar spine, degenerative changes, dysfunctions Results: Currently, in addition to injuries and mechanical loads, the causes of lumbar spine dysfunction also include abnormal spinal nutritional composition and genetic factors, with the greatest emphasis on genes encoding type 1 collagen. During diagnostics, apart from X-ray imaging, computed tomography and resonance imaging methods should not forget about properly conducted interviews and functional tests. Kinesitherapy assisted by physical treatment methods such as laser therapy or ultrasound should play a major role in rehabilitation. Kinesitherapy should be tailored to the individual patient, and exercises selected so that the patient can also do them at home. Conclusions: In the prevention of degenerative changes of the lumbar spine, there should be a much greater emphasis on patient education related to risk factors or learning ergonomic work. Despite much work on this topic, there is still a need to improve public awareness and further research on prevention.